Would community conservation initiatives benefit from external financial oversight? A framed field experiment in Namibia's communal conservancies. (June 2021) - Turpie, Jane; Letley, Gwyneth
Highlights: People had low confidence in conservancy management institutions and expressed a desire for oversight. Co-operation increased with external financial oversight, particularly when trust in the community institution was low. External financial oversight was more effective than payment level in increasing cooperation. Abstract: It is commonly asserted that the successful management of common property resources (CPR), and by extension, the provision of public goods such as biodiversity and carbon, requires the devolution of control to local communities. However, where trust in community institutions is low, the intrinsic motivation to co-operate may be diminished. In this study, we carried out surveys and framed field experiments on the introduction of payments for ecosystem services (PES) to Namibia's communal conservancies, established under the community-based natural resource management (CBNRM) programme. We used a threshold public good game where income from conservation efforts would require cooperation in terms of investing in conservation management and thereby also sacrificing opportunities to use designated wildlife areas. Our study found that households had low confidence in the conservancy management institutions and were more willing to co-operate when external financial oversight was provided. In fact, addressing the risk of financial mismanagement was more important than the payment level. Participants with a low level of confidence in the conservancy management contributed significantly less, but the gap narrowed when oversight was introduced. This suggests that initiatives to incentivise conservation of communally-owned land may require the close involvement of trustworthy external organisations to ensure their effectiveness.